(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, mulberry leaves, silkworms, cocoons and their waste were selected as samples. Inductively coupled plasma optical emission spectrometry studied the quantities of 30 different elements. When comparing the mineral composition of the samples, it was found that there is a sharp difference in macroelements in the amount of potassium, calcium, and magnesium, as well as the absence of barium from microelements in the silkworm, and only lead was found among toxic elements in all samples. Studying the degree of absorption of minerals from silkworm leaves and their content in silkworm waste is one of the current problems. When comparing the mineral composition of mulberry leaves and silkworms feeding on these leaves, and the waste generated as a result of digestion, from macroelements there is a sharp difference in the amount of potassium, calcium and magnesium, from microelements there is no barium in the silkworm, and it has also been established that the amount of toxic elements have similar meanings.